Effects of organophosphorated pesticides on the hepatiologic health of people and the environment in Paiján. 2019 (SCIÉNDO INGENIUM, 2022)
In order to verify the effects of organophosphate pesticides on the hepatological health of people and the environment in Paiján, an explanatory-analytical research of a qualitative, phenomenological and clinical-epidemiological nature was carried out in four steps: Explore and understand the phenomenon in its context; analyze it as a historical medical-social problem; check the phenomenon as a current social medical problem and; identify the level of understanding and recognition of the phenomenon in the current social ideology that implies analysis of the perspective of damage. The geo-socioeconomic and demographic profile of the population, the usability of organophosphate pesticides, the behavior of the intoxication indicators, the results of laboratory samples on the hepatological health of people and the environment, as well as the little understanding and recognition of hepatological health problems and the environment by the community, have meant that the harmful effects of organophosphate pesticides are not products of evolutionary free will of usability phenomena, but are contained in the evolutionary development of the general and peaceful context in which the communities of La Arenita, Macabi Alto and La Pampa live and develop, in the District of Paiján
Keywords: Organophosphate pesticides; Liver health of people; environment; Epidemiological; Harmful effects